Ectopic pregnancy: chorion villi histologic patterns. Preliminary report - Pereda Garay, José (2015)
OBJECTIVES. To describe ectopic pregnancy chorion villi histological patterns. DESIGN. Descriptive, retrospective anatomic and pathologic study. SETTING. Pathology Department, Maternal Perinatal National Institute, Lima, Peru (INMP). BIOLOGIC MATERIAL. Ectopic pregnancies chorion villi. INTERVENTIONS. The histological characteristics of a series of 98 ectopic pregnancies from the files of the Department of Pathology were studied. MAIN OUTCOMEMEASURES. Histological patterns of chorion villi.RESULTS. We describe five different histological patterns of chorial villi. CONCLUSIONS. The possibility that these chorial villi histology changes are related to materno-fetal pathology is considered.